2003
DOI: 10.1074/jbc.m303147200
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding Protein Family Members Recruit the Coactivator CREB-binding Protein and Trigger Its Phosphorylation

Abstract: CCAAT/enhancer-binding protein (C/EBP) family members are transcription factors involved in important physiological processes, such as cellular proliferation and differentiation, regulation of energy homeostasis, inflammation, and hematopoiesis. Transcriptional activation by C/EBP␣ and C/EBP␤ involves the coactivators CREB-binding protein (CBP) and p300, which promote transcription by acetylating histones and recruiting basal transcription factors. In this study, we show that C/EBP␦ is also using CBP as a coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 70 publications
2
119
0
1
Order By: Relevance
“…The current paradigm of CBP/p300 action suggests that CBP/p300 activity is mediated by competition of various promoter elements for limited quantities of CBP/p300. However, recent studies suggest that the activity of CBP may also be controlled by phosphorylation, although correlation between specific sites of phosphorylation and alteration of function has been rare (Kovacs et al, 2003). Given our recent observations regarding (1) the role of AKT in regulating Tam-induced apoptosis and (2) Tam-modulated CBP recruitment to the IRF-1 GAS element, we are currently investigating the potential role of AKT in promoting CBP recruitment and IRF-1 induction.…”
Section: Discussionmentioning
confidence: 99%
“…The current paradigm of CBP/p300 action suggests that CBP/p300 activity is mediated by competition of various promoter elements for limited quantities of CBP/p300. However, recent studies suggest that the activity of CBP may also be controlled by phosphorylation, although correlation between specific sites of phosphorylation and alteration of function has been rare (Kovacs et al, 2003). Given our recent observations regarding (1) the role of AKT in regulating Tam-induced apoptosis and (2) Tam-modulated CBP recruitment to the IRF-1 GAS element, we are currently investigating the potential role of AKT in promoting CBP recruitment and IRF-1 induction.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that C/EBPa, C/EBPb, and C/EBPd interact with the ET-1 promoter in the genomic regions displaying the predicted elements. It is noteworthy that in addition to the canonical interactions, several mechanisms of C/EBP-induced gene transcription have been demonstrated including interplays with other transcription factors such as (NF-kB, AP-1, Sp1, CREB) [37][38][39][40] or recruitment of various transcriptional co-regulators that affect chromatin conformation, a condition that untimely facilitates the trapping of basal transcription factors. [41,42] Based on that fact that NF-kB and AP-1 are direct regulators of ET-1 transcription, the existence of non-canonical associations among transcriptional complexes formed by heterodimers consisting of C/EBP and other transcription factors that might or might not contain the basicleucine zipper domain [18] should be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…The Gal4-Luc reporter gene is described in ref. 38. pcDNA3-GAL-CREB constructs are described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%